Poetry American, British, world - Seltzer, Richard (B%R Samizdat Express, 2002)
This CD-ROM contains 303 books in the public domain by 135 poets presented in plain text format, inthe follwing broad classifications: American (US) poetry, Arabic poetry, Australian poetry, Canadian poetry, English poetry anthologies, English poetry medieval, English poetry 14th century, English poetry 16th century, English poetry 17th century, English poetry 18th century, English poetry 19th century and later, Finnish poetry, French poetry, German poetry, Greek poetry, Indian poetry, Irish poetry, Italian poetry, Latin/Roman poetry, Scottish poetry, Welsh poetry.